2004
DOI: 10.1038/nature03137
|View full text |Cite
|
Sign up to set email alerts
|

Meteoric smoke fallout over the Holocene epoch revealed by iridium and platinum in Greenland ice

Abstract: An iridium anomaly at the Cretaceous/Tertiary boundary layer has been attributed to an extraterrestrial body that struck the Earth some 65 million years ago. It has been suggested that, during this event, the carrier of iridium was probably a micrometre-sized silicate-enclosed aggregate or the nanophase material of the vaporized impactor. But the fate of platinum-group elements (such as iridium) that regularly enter the atmosphere via ablating meteoroids remains largely unknown. Here we report a record of irid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
149
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(158 citation statements)
references
References 29 publications
9
149
0
Order By: Relevance
“…It is interesting to compare rocket particulate emissions to incoming cosmic dust from space that also affect the stratosphere. The influx of meteoritic dust is about 20 kt per year [Bardeen et al, 2008;Gabrielli et al, 2004] while rockets currently emit about 5 kt of submicron particulate.…”
Section: Emissionsmentioning
confidence: 99%
“…It is interesting to compare rocket particulate emissions to incoming cosmic dust from space that also affect the stratosphere. The influx of meteoritic dust is about 20 kt per year [Bardeen et al, 2008;Gabrielli et al, 2004] while rockets currently emit about 5 kt of submicron particulate.…”
Section: Emissionsmentioning
confidence: 99%
“…The estimates of how much meteoric material enters the earth's atmosphere vary from 5 to 400 tons/day (Gabrielli et al, 2004;Love and Brownlee, 1993;Mathews et al, 2001;Ceplecha et al, 1998). There are two reasons for this wide spread of estimates.…”
Section: Amount Of Meteoric Materialsmentioning
confidence: 99%
“…Despite their tiny dimensions, it has been suggested that MSPs play a significant role in a host of atmospheric phenomena such as the nucleation of noctilucent clouds, the mesospheric metal atom chemistry, the transport of meteoric material to the ground, and the formation of nitric acid trihydrate-particles in polar stratospheric clouds [e.g., Plane, 2003;Gabrielli et al, 2004;Voigt et al, 2005]. However, due to the above mentioned tiny dimensions, measurements of MSPs have been very difficult to obtain.…”
Section: Introductionmentioning
confidence: 99%